Adoption of Ritual and Poetry of Aláwòrò-Ẹkùn Deity in Combating Regional Instability in Nigeria - Rifqat Opeyemi Sanni (JURNAL ARBITRER, 2023)
The paper examines the Adoption of ritual and poetry of Aláwòrò-Ẹkùn deity in combating regional instability in Nigeria. This was done with a view of projecting deity and its rituals as a means of resolving conflicts and instability in the society. The study makes use of in-depth interviews with four selected participants from Aláwòrò-Ẹkùn worshippers (one priests and three followers). These participants were selected from Arárọ̀mí-Ale one of the Àwórì communities in Lagos State. Audio-visual and photographic recordings were used for documentation of symbolic elements and oral performances at the shrines. The findings showed that ritual and poetry is an effective method to combat regional instability in Nigeria. It increases cooperation, trust and foster a sense of solidarity among neighboring communities. Also, it showed this deity as a savior that rescued people of Ọ̀jọ́ community in Lagos State and its environment from robbers, kidnapers, terrorist and the epidemic of 1935. The poetry becomes the means of communicating with the deity to fish out traitors and the aggrieved ones before sacrifices. The study concluded that Aláwòrò-Ẹkùn deity had played crucial roles right from the ancestral period by ensuring safety of Ọ̀jọ́ and Arárọ̀mí-Ale community. It also pointed to the fact that Aláwòrò-Ẹkùn deity is the pillar of peaceful co-existence and unity in Arárọ̀mí-Ale and Ọ̀jọ́ community. The followers were compelled to settle their grievance and grudges before appearing in Aláwòrò-Ẹkùn shine. If this is generally accepted, prolonged grudges or disagreement that may lead to instability in the community will be resolved and instability will be prevented. The findings showed that the adoption of ritual and poetry is an effective method to combat regional instability in Nigeria.